Klippning i klena gallringar : prestationsstudie av Forest ebeaver - Key, Jesper (SLU/School for Forest Management, 2012)
Forest ebeaver is, equipped as a bio-energy harvester, approximately four and a half meter long and weigh just over two tons. The main purpose of this report is to find out whether a small machine like Forest ebeaver can be profitable used in early thinning. To find this out a study has been made using the machine to thin in a young pine stand.